Getting in and Staying Alive: Role for Coronin 1 in the Survival of Pathogenic Mycobacteria and Naïve T Cells - Mori, Mayumi; Pieters, Jean (Frontiers in Immunology, 2018)
There are many different pathogenic stimuli that are able to activate the immune system, ranging from microbes that include bacteria, viruses, fungi and parasites to host-derived triggers such as autoantigens that can induce autoimmunity and neoantigens involved in tumorigenesis. One of the key interactions shaping immunity towards these triggers involves the encounter of antigen processing and presenting cells such as macrophages and dendritic cells with T cells, resulting in immune responses that are highly selective for the antigenic trigger. Research over the past few years has implicated members of the coronin protein family, in particular coronin 1, in responses against several pathogenic triggers. While coronin 1 was initially described as a host factor allowing the intracellular survival of the pathogen Mycobacterium tuberculosis, subsequent work showed it to be a crucial factor for naïve T cell homeostasis. The activity of coronin 1 in allowing the intracellular survival of pathogenic mycobacteria is relatively well characterized, involving the activation of the Ca2+/calcineurin pathway, while coronin 1’s role in modulating naïve T cell homeostasis remains more enigmatic. In this Minireview we discuss the knowledge on the role for coronin 1 in immune cell functioning and provide a number of potential scenarios via which coronin 1 may be able to regulate naïve T cell homeostasis.